On the Wings of Myth. A Review of Serge Dunis’s Pacific Mythology (Altre Modernità, 2013)
This article follows the steps of Serge Dunis’s book Pacifc Mythology, Ty Name Is Woman; a complex work, arguing that the settlement of the Pacifc has happened from West to East, relying on a broad variety of studies and disciplines. The author of this book operates a multifaceted investigation of all the aspects that could favour a better understanding of how the Pacifc has come to life, of how the frst settlers have reached these far-away islands, and of how their cultural background has influenced the new cultures that were born here. Setting out on the vast ocean of anthropological research, as the settlers of these islands had set out on the Pacifc Ocean, reaching all the way across, Dunis has given us the opportunity to land on aunknown country, where the settlement from West to East of the Pacifc becomes a fact, supported by a complex amount of evidence, ranging from archaeology to meteorology, from geography to anthropology. And, although “the challenges of 'Oceanian Mythology' undoubtedly overcome those of this work and it will take some more time to validate their scientifc validity”, as Raymond Mayer writes, “Dunis has certainly opened the way”. And he especially has shown that “nature and cultureare [...] never at rest”, and that “objects and plants never travel on their own: the cultural side is part and parcel of the package”.